HIV/AIDS and Croatian Migrant Workers - Štulhofer, Aleksandar (Array, 2006)
Due to their geographical mobility and long periods of separation from intimate partners, migrant workers are at increased risk for a variety of sexually transmitted infections (STIs) including HIV/AIDS. This study sought to investigate patterns in HIV/AIDS related knowledge, attitudes and sexual behaviour in migrant workers in Croatia. In 2003, 566 male migrant workers were recruited during regular required medical examinations and surveyed at seven locations throughout the country. Each participant was asked to complete a self-administered KABP (sexual knowledge, attitudes, beliefs and practices) questionnaire. The average age of respondents was 38.2 years and the majority worked as seafarers (77.3%) and construction workers (20.5%). Only 18.5% of respondents were able to correctly answer all 13 questions assessing knowledge of HIV/AIDS. Seafarers reported higher levels of knowledge than did construction workers. The average respondent reported having had two sexual partners in the last 12 months, with slightly over half of the respondents (55.3%) reporting condom use at their last intercourse with a casual partner. One fifth of the respondents (20.3%) who reported having had intercourse with a sex worker during the last year reported not using condoms at last intercourse. The number of sexual partners was correlated with age, marital status, faith in God, and personal HIV risk assessment. Attitudes toward condom use, co-workers’ HIV/AIDS concerns and the duration of migrant status (within the last two years) were shown to be significant correlates of condom use at last intercourse with a casual partner. The effect of HIV/AIDS related knowledge on analyzed behaviors did not reach statistical significance. Inadequate patterns of migrant workers’ condom use, gaps in knowledge about HIV transmission and modes of protection, as well as widespread ignorance regarding available anonymous HIV testing found by this study suggest a critical need for expert intervention to avert the potential for an increase in new HIV/AIDS cases. A coordinated, systematic campaign for HIV/AIDS prevention among Croatian migrant workers should focus on increasing peer communication about HIV/AIDS, especially among younger migrant workers, and on reducing the frequency of sexual risk taking.